2021
DOI: 10.1155/2021/5573628
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identifying m6A Regulators as an Independent Prognostic Biomarker in Pancreatic Cancer Based on The Cancer Genome Atlas Database

Abstract: Background. Pancreatic cancer is one of the most malignant tumors of the digestive system, and its treatment has rarely progressed for the last two decades. Studies on m6A regulators for the past few years have seemingly provided a novel approach for malignant tumor therapy. m6A-related factors may be potential biomarkers and therapeutic targets. This research is focused on the gene characteristics and clinical values of m6A regulators in predicting prognosis in pancreatic cancer. Methods. In our study, we obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To accurately detect the expression of m6A regulators in PAAD, we integrated seven independent datasets, with a total of 930 patients with PAAD. Although M6A-related regulators have been reported in pancreatic cancer (23,24). Geng et al reported m6A-related genes and m6A RNA methylation regulators in PAAD and their prognostic performance based on TCGA database (25).…”
Section: Discussionmentioning
confidence: 99%
“…To accurately detect the expression of m6A regulators in PAAD, we integrated seven independent datasets, with a total of 930 patients with PAAD. Although M6A-related regulators have been reported in pancreatic cancer (23,24). Geng et al reported m6A-related genes and m6A RNA methylation regulators in PAAD and their prognostic performance based on TCGA database (25).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of these amplification and deletion events is therefore one of the main goals of medical genetics research. Indeed, CNVs have been observed in patients with pancreatic ductal adenocarcinoma (PDAC) [74][75][76][77][179][180][181][182][183][184][185][186][187]. However, the detection of CNVs and their subsequent association with functional and clinical phenotypes remains very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CNVs have been observed in patients with pancreatic ductal adenocarcinoma (PDAC) [ 74 , 75 , 76 , 77 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ]. However, the detection of CNVs and their subsequent association with functional and clinical phenotypes remains very challenging.…”
Section: Discussionmentioning
confidence: 99%